(untitled) (Ottawa, 1999)
Conflict over natural resources – such as land, water and forests – has for ages been widespread. Whether it be a local dispute between neighboring farmers or an international debate over shared resources (such as waterways), people everywhere compete for the natural resources they need to ensure or enhance their quality of life. The conflict may unfold as a simple war of words, or it may escalate to armed confrontation with loss of life. Cultivating Peace presents original case studies from Africa, Asia and Latin America, which describe important experience on moving from conflict to collaborative modes of management. The accompanying essays draw on the case studies, grounding theory in hard-won experience.
Quản lý tài nguyên thiên nhiên và suy nghĩ hệ thống,Xã hội học môi trường
Keywords: Natural resources,Tài nguyên thiên nhiên; Developing countries,Management